The expression of limb gap genes in the mite Archegozetes longisetosus reveals differential patterning mechanisms in chelicerates. Issue 4 (1st July 2013) - Barnett, Austen A.; Thomas, Richard H.
SUMMARY The modular organization of arthropod limbs has lead to the evolution of a diversity of appendages within this phylum. A conserved trait within the arthropods is the utilization of a conserved set of regulatory genes that specify the appendage podomeres along the proximo‐distal axis, termed the limb gap genes. These include extradenticle, homothorax, dachshund, and Distal‐less. The deployment of these genes in the most basally branching arthropod group, the chelicerates, has only been studied in detail in two chelicerate groups, the harvestmen and spiders. Given the broad range of appendage diversity within the chelicerates, comparative studies of gap gene deployment in other chelicerates groups is needed. We therefore followed limb gap gene expression in a member of the largest chelicerate group, Acari, the oribatid mite Archegozetes longisetosus. We show that in contrast to many arthropod species, A. longisetosus expresses homothorax and extradenticle exclusively in the proximal portion of the appendages, which refutes the hypothesis of a sister‐group relationship between chelicerates and myriapods. We also provide evidence that mites posses the ancestral chelicerate condition of possessing three‐segmented chelicerae, which also express the gene dachshund. This adds support to the hypothesis that a cheliceral dachshund domain is ancestral to arachnids. Lastly, we provide evidence that the suppression of the fourth pair of walking legs, a putative synapomorphy for Acari, is accomplished by repressing the development of the medial and distal regions of the limb.